Structural model of Longkou oil shale kerogen and the evolution process under steam pyrolysis based on ReaxFF molecular dynamics simulation. Issue 2 (17th January 2021) - Zhang, Zhijun; Chai, Jun; Zhang, Hanyu; Guo, Liting; Zhan, Jin-Hui
ABSTRACT: The product distribution and reaction mechanism of steam pyrolysis of Longkou oil shale kerogen was researched by molecular dynamics simulation. Molecule structural model used in the simulation was constructed according to the analysis results of a series of detection about kerogen extracted from Longkou oil shale. Reactive force field molecular dynamics (ReaxFF MD) was used to simulate both steam pyrolysis and direct pyrolysis process of the kerogen at the temperature of 1600, 2000, 2400 and 2800 K. The results show that temperature is a critical factor affecting product distribution in steam pyrolysis, and 2000 K is a proper set temperature for studying steam pyrolysis via molecular simulation method. Besides that, adding the H2 O molecules during steam pyrolysis can form complexes with heterogeneous atoms, thus destroying the intermolecular interactions in kerogen. Moreover, as the hydrogen radicals come from H2 O molecules can inhibit cross-linking reactions between small fractions, it can reduce the average molecular weight of organic molecules product. These conclusions could be helpful for rational use of oil shale.